Stratifikasi Sosial Warga Binaan Wanita di Rutan Pondok Bambu - Kartikawati, Reni (Masyarakat: Jurnal Sosiologi, 2012)
Basically, social stratification does not occur in a total institution like detention. If it does, it only occurs between the officers and the convicts. However, social stratification apparently occurs among female convicts in Rutan Pondok Bambu. Based on that fact, this research tried to discover the real image of social stratification in Rutan Pondok Bambu; the factors that form the social stratification, and the people who form that social stratification. By using qualitative approach, this research showed that social stratification does occur among convicts in Rutan Pondok Bambu, which, at some level, is the same with the stratification found in general society. Moreover, this research also found four dimensions of social stratification in Rutan Pondok Bambu. They are power, prestige, privilege, and skill dimensions of female convicts in that rutan. Related to that phenomenon, people who form the social stratification in that rutan are the officers as the technical executives, who indirectly affect the “culture” among female convicts in the rutan in forming the social stratification.